1999
DOI: 10.1046/j.1365-313x.1999.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

ACGT‐containing abscisic acid response element (ABRE) and coupling element 3 (CE3) are functionally equivalent

Abstract: SummaryACGT-containing ABA response elements (ABREs) have been functionally identi®ed in the promoters of various genes. In addition, single copies of ABRE have been found to require a cis-acting, coupling element to achieve ABA induction. A coupling element 3 (CE3) sequence, originally identi®ed as such in the barley HVA1 promoter, is found approximately 30 bp downstream of motif A (ACGT-containing ABRE) in the promoter of the Osem gene. The relationship between these two elements was further de®ned by linker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(187 citation statements)
references
References 50 publications
(88 reference statements)
9
177
0
1
Order By: Relevance
“…By analyzing the promoter sequences of this combined list of genes induced by our electrical impulses, we found four distinct classes of short DNA motif that appeared at a frequency statistically higher than in the genome as a whole (Table 2, Figure 2). These four motifs most closely resembled motifs already described in the plant molecular biology literature, namely the CRT/DRE coldand drought-responsive element (Yamaguchi-Shinozaki and Shinozaki, 1994;Stockinger et al, 1997;Liu et al, 1998), the ABRE abscisic acid response element (Hobo et al, 1999), the binding site of the CAMTA transcription factors (which we have named CAM box) (Yang and Poovaiah, 2002), and finally the Site II motif (Tré mousaygue et al, 2003). The ABRE (CACGTGT) and CAM box (ACGCGT) completely fit the consensus of the ABRE (CACGTG[T/C/G]) and ABRE coupling element ([C/A]ACGCG[T/ C/A]) identified by our previous microarray experiment (Kaplan et al, 2006).…”
Section: Identification Of Four Promoter Motifs That Are Overrepresensupporting
confidence: 70%
See 1 more Smart Citation
“…By analyzing the promoter sequences of this combined list of genes induced by our electrical impulses, we found four distinct classes of short DNA motif that appeared at a frequency statistically higher than in the genome as a whole (Table 2, Figure 2). These four motifs most closely resembled motifs already described in the plant molecular biology literature, namely the CRT/DRE coldand drought-responsive element (Yamaguchi-Shinozaki and Shinozaki, 1994;Stockinger et al, 1997;Liu et al, 1998), the ABRE abscisic acid response element (Hobo et al, 1999), the binding site of the CAMTA transcription factors (which we have named CAM box) (Yang and Poovaiah, 2002), and finally the Site II motif (Tré mousaygue et al, 2003). The ABRE (CACGTGT) and CAM box (ACGCGT) completely fit the consensus of the ABRE (CACGTG[T/C/G]) and ABRE coupling element ([C/A]ACGCG[T/ C/A]) identified by our previous microarray experiment (Kaplan et al, 2006).…”
Section: Identification Of Four Promoter Motifs That Are Overrepresensupporting
confidence: 70%
“…It is not clear what other signals induce the CAM box, although a role for the CAMTA transcription factors that bind this motif has also been shown in response to pathogens and auxin (Galon et al, 2008;Du et al, 2009;Galon et al, 2010b), which also provoke elevations in [Ca 2+ ] c (Felle, 1988;Knight et al, 1996;Grant et al, 2000). The CRT element is also induced in response to drought (Liu et al, 1998), and the ABRE is induced in response to ABA and drought (Hobo et al, 1999), which both induce [Ca 2+ ] c (McAinsh et al, 1990;Knight et al, 1996;Knight et al, 1997). It is not clear in which calcium-regulated process the Site II motif participates; therefore, correlating these conditions with [Ca 2+ ] c elevations is not currently possible.…”
Section: Identification Of Four Promoter Motifs That Are Overrepresenmentioning
confidence: 99%
“…A combination of ABRE/CE3-like motifs was initially thought to establish a minimal ABA-responsive complex to confer ABA responsiveness (Shen and Ho, 1995;Shen et al, 1996). In fact, it was later shown that the ACGT-containing ABREs and CE3 are functionally equivalent cis-acting elements and that multiple ABREs or CEs or the combination of ABREs with CEs can also confer ABA responsiveness (Hobo et al, 1999). In our analysis, it is interesting that while ABREs elements were practically absent in the promoters of BAM1 orthologs from monocotyledons, the CE3-like motifs were universally present ( Figure 8B).…”
Section: Abres Are Conserved In the Promoters Of Bam1 Orthologsmentioning
confidence: 99%
“…A cis-acting motif CE3 (GACGCGTGTC) was found in SPS promoter involved in ABA (absicisic acid) and VP1 responsiveness. These motifs found to interact with ABRE motifs required for ABA and VP1 related expression (Hobo et al, 1999).A unique motif in SPS promoter was HDZIP2ATATAHB2 interacts with athb2 and reported to be involved in morphological changes (Ohgishi et al, 2001). This cis-acting motif was found to present in cotton PROTODERMALFACTOR1 gene promoter that derives fiber specific expression during initiation and early elongation phase (Deng et al, 2012).Presence of various light regulated motifs and pathogenic responsive sequences also depicted that this promoter may be induced by light.…”
Section: Discussionmentioning
confidence: 99%